Male reproduction in the polluted environment – review - Nagy, Szabolcs (Acta Agraria Kaposváriensis, 2014)
Endocrine Disrupting Chemicals (EDC-s) present in the environment can cause disturbance in the reproductive biology of animals and humans. While most of the studies focus on the adverse effects on the hormonal system, recent findings indicate a direct effect on germ cells. The present review introduces laboratory assays used to study several structural and physiological aspects of spermatozoa exposed to EDC-s.
Keywords: environment; endocrine disrupting chemicals; reproduction; sperm; low cytometry